Evaluation of two ELISA methods to detect therapeutic anti-IGF1R antibodies in clinical study samples of dalotuzumab. (September 2011) - Yin, Kuo-Chang; Chen, Dave; Bakhtiar, Ray; Verch, Thorsten
Background: Dalotuzumab (MK 0646), an anti-IGF1R antibody intended for cancer therapy, has progressed to Phase III clinical trials. To evaluate pharmacokinetic properties, we developed and compared two ELISAs to measure dalotuzumab in human serum and validated the second method following regulatory guidelines for ligand-binding assays.Results: After an IGF1R-mediated capture step, dalotuzumab was detected by either an antihuman IgGFc- or by an antihuman IgG1-specific antibody. The assay range was 20 to 2000 ng/ml with mean inter-day accuracy of controls ranging from 97 to 108% (method A) and 83 to 97% (method B), respectively. Mean assay precision was ≤20% CV both intra- and inter-day. Other parameters that were validated included dilution linearity, stability, interferences and incurred sample reanalysis. In addition, application of both assay formats to clinical sample analysis was demonstrated establishing time–concentration curves.Conclusion: As the methods rely on commercial reagents, they may be applicable to other anti-IGF1R antibodies and facilitate the development of new therapeutics.